2023
DOI: 10.1002/cctc.202201626
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Decomposition in Electric Field over Ce‐based Materials

Abstract: Electric field‐induced decomposition of ammonia into hydrogen and nitrogen was investigated over CeO2, Fe‐, Ru‐ deposited CeO2, CePO4 and Sr‐doped CePO4, and CeZrO4 in a packed bed down‐flow reactor. The effect of applied current, concentration of ammonia in a feed, and residence time was examined using CeO2 alone. The conversion of ammonia was also studied with respect to a reduction temperature, loading and a type of the deposited metal. The activity results have been analyzed in terms of surface, morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
(104 reference statements)
0
7
0
Order By: Relevance
“…Additionally, reports have shown that adding an inert gas such as Ar increases the electron energy and enhances the electric field . This increases electron impact reaction with gas phase molecules and promotes plasma-phase chemistry. There is also the potential to create metastable species, which undergo Penning ionization through impact collision and energy exchange with neutral species such as NH 3 . , …”
Section: Plasma Catalysis For Hydrogen Generationmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, reports have shown that adding an inert gas such as Ar increases the electron energy and enhances the electric field . This increases electron impact reaction with gas phase molecules and promotes plasma-phase chemistry. There is also the potential to create metastable species, which undergo Penning ionization through impact collision and energy exchange with neutral species such as NH 3 . , …”
Section: Plasma Catalysis For Hydrogen Generationmentioning
confidence: 99%
“…296−298 There is also the potential to create metastable species, which undergo Penning ionization through impact collision and energy exchange with neutral species such as NH 3 . 196,299 Fateev et al 299 demonstrated the influence of diluent when they investigated the plasma decomposition of an NH 3 /Ar stream. The authors studied different NH 3 composition ranges (0.1−10%) and observed that in the lower concentration…”
Section: Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…One approach to improving the activity of these catalyst systems is to use rare earth element-based heteroatoms, such as La and Ce, for doping. This results in improving the surface properties, increasing the number of active sites, and enhancing the catalytic activity of Fe and Ni-based catalysts [ 39 , 40 , 41 , 42 , 43 ]. Another approach is to create multi-metal alloy-based structures, which can further enhance the catalytic activity by providing better dispersion of the metal atoms, improving the stability of the catalyst, and increasing the resistance to poisoning [ 28 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Categories Of Nh 3 Decompositionmentioning
confidence: 99%